2021
DOI: 10.1101/2021.06.04.21258358
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pre-infection 25-hydroxyvitamin D3 levels and association with severity of COVID-19 illness

Abstract: Objective: Studies have demonstrated a potential link between low vitamin D levels and both an increased risk of infection with SARS-CoV-2 and poorer clinical outcomes but have not established temporality. This retrospective study examined if, and to what degree, a relationship exists between pre-infection serum vitamin D levels and disease severity and mortality of SARS-CoV-19. Design and patients: The records of individuals admitted between April 7th, 2020 and February 4th, 2021 to the Galilee Medical Cen… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 29 publications
0
33
0
1
Order By: Relevance
“…The proposed mechanism involves a direct stimulation of insulin-producing pancreatic cells via their vitamin D receptors and an indirect stimulation via normalization of systemic calcium levels, allowing appropriate calcium-induced insulin secretion ( 83 ). Despite there being no clinical trials demonstrating that low Vitamin D levels lead to higher SARS-CoV-2 susceptibility, there have been numerous studies showing that the pre-infection Vitamin D deficiency is associated with increased morbidity and mortality and hence lower Vitamin D levels are likely a good predictor for disease progression ( 84 ).…”
Section: Role Of Vitamin D and Glutathione In Decreasing Cytokine Sur...mentioning
confidence: 99%
“…The proposed mechanism involves a direct stimulation of insulin-producing pancreatic cells via their vitamin D receptors and an indirect stimulation via normalization of systemic calcium levels, allowing appropriate calcium-induced insulin secretion ( 83 ). Despite there being no clinical trials demonstrating that low Vitamin D levels lead to higher SARS-CoV-2 susceptibility, there have been numerous studies showing that the pre-infection Vitamin D deficiency is associated with increased morbidity and mortality and hence lower Vitamin D levels are likely a good predictor for disease progression ( 84 ).…”
Section: Role Of Vitamin D and Glutathione In Decreasing Cytokine Sur...mentioning
confidence: 99%
“…There is evidence in the literature that insufficient serum vitamin D levels are associated with an increased risk of acute respiratory infections, including the COVID‐19 disease [15a–d] . Several studies suggested that taking vitamin D 3 (see Figure 1) [15e] may have a positive effect on the course of SARS‐CoV‐2 infections and provided strong evidence of a causal relationship between low vitamin D status and an increased risk of severe COVID‐19 disease [15a–c] . Due to a lot of encouraging data, the use of vitamin D to reduce the severity of SARS‐CoV‐2 infections is receiving considerable attention.…”
Section: Figurementioning
confidence: 99%
“…Additionally, hypovitaminosis D was found to be an independent risk factor for SARS-CoV-2 infection and hospitalization due to COVID-19 after adjustment for demographic variables (age, gender, and BMI) and comorbidities [ 70 ]. A recent study has shown that pre-infection vitamin D deficiency was associated with increased COVID-19 severity, independently of age, gender, BMI, and comorbidities and also with higher mortality due to COVID-19 [ 71 ]. Of note, the researchers used a cosinor model to account for any influence of the seasonal variation of vitamin D status.…”
Section: Hypovitaminosis D and Covid-19mentioning
confidence: 99%
“…Hypovitaminosis D is an independent risk factor for SARS-CoV-2 infection and hospitalization [ 70 , 71 ]…”
Section: Hypovitaminosis D At the Intersection Of Obesity And Covid-19mentioning
confidence: 99%